Counseling Acceptance Skills School Counselor In Individual Counseling - Mirda Yolanda; Fadhillah Yusri; Junaidi Junaidi (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2021)
The purpose of this study is that researchers want to look at counselee acceptance skills in individual counseling by guidance and counseling teachers in MTsN 10 Agam. This type of research is descriptive qualitative field research. The key informants of this study were 1 guidance and counseling teacher plus a supporting informant of 7 students who had participated in individual counseling using the snowball method, which is a method for identifying, selecting and taking samples in a network or continuous chain of relationships. The information obtained will be developed to the point of saturation so that the longer the more information obtained. Based on the results of research and discussion it can be concluded that as a strategy for counselee acceptance skills by counseling teachers in individual counseling, counseling teachers assume counselee is the closest person, can accept counselees openly, guiding sincerely or voluntarily, sincerity, and loving, keep secrets counselee, not discriminating counselee, and love counseling.